Detection of Glaucoma in a Cohort of Chinese Subjects with Systemic Hypertension. (14th January 2013) - Gangwani, Rita A.; Chan, Jonathan; Lee, Jacky; Kwong, Alfred; Lai, Jimmy S. M.
Abstract : Purpose . To determine the presence and type of glaucoma in a cohort of adult Chinese subjects with systemic hypertension. Methods . This prospective cohort study included 200 hypertensive Chinese adults aged >40 years old who underwent screening via frequency doubling technology (FDT) perimetry and intraocular pressure (IOP) measurement by noncontact tonometry (NCT) in a general outpatient clinic. Those with IOP > 21 mmHg and/or visual field (VF) defects on FDT were referred for complete ophthalmological examination. The diagnosis of glaucoma was based on an abnormal VF on Humphrey Field Analyzer (HFA) by Hodapp-Parrish-Anderson's criteria and an increased vertical cup-disc ratio (VCDR). Results . The mean age of the subjects was 64.66 ± 9.47 years, and the male:female ratio was 92 : 108. All patients were hypertensive with a mean blood pressure (BP) of 131.1 ± 15.1 / 76.6 ± 11.1 mmHg whilst on systemic antihypertensive medication. Of the 111 patients that had an abnormal initial screening, 14 (7.9%) were confirmed to have glaucoma with the highest prevalence of normal tension glaucoma (NTG) (6.2%), followed by primary angle closure glaucoma (PACG) (1.1%) and primary open angle glaucoma (POAG) (0.5%). The positive predictive value of FDT perimetry was 71%. Conclusion . Nearly 8% of the adults with systemic hypertension had glaucoma, and NTG was the most prevalent type.